2012
DOI: 10.1901/jaba.2012.45-69
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Self‐instruction Package for Conducting Stimulus Preference Assessments

Abstract: Research suggests that inexperienced individuals cannot accurately implement stimulus preference assessments given written instructions alone. Training that includes written instructions supplemented with feedback from a professional with expertise in conducting preference assessments has proven effective; unfortunately, expert-facilitated direct training may not be widely available. In the current study, we used multiple baseline designs to evaluate the efficacy of an antecedent-only self-instructional packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 14 publications
8
99
1
Order By: Relevance
“…Self-instruction involves a staff member reading an instructional manual, responding to content-related quiz items, receiving delayed feedback on the accuracy of her quiz performance, and sometimes viewing videotaped models (Salem et al, 2009) or rehearsing the procedures with a 'pretend client' (Thiessen et al, 2009) before she or he has the supervised opportunity to use the procedures. Clear guidelines are not yet available for constructing SI manuals, but past researchers have suggested that trainers should prepare materials with nontechnical language and supplemental diagrams that illustrate the progression of steps or guidelines for arranging the materials (e.g., Graff & Karsten, 2012;Severtson & Carr, 2012). Self-instruction may be delivered in a computer-based format in which quizzes are embedded and staff members receive immediate, automated feedback on their answers; trainers can also program computer-based instruction such that staff members may not advance to later content without mastering earlier content (e.g., Nosik et al, 2013).…”
Section: Self-instruction Description and Rationale For Self-instructionmentioning
confidence: 99%
“…Self-instruction involves a staff member reading an instructional manual, responding to content-related quiz items, receiving delayed feedback on the accuracy of her quiz performance, and sometimes viewing videotaped models (Salem et al, 2009) or rehearsing the procedures with a 'pretend client' (Thiessen et al, 2009) before she or he has the supervised opportunity to use the procedures. Clear guidelines are not yet available for constructing SI manuals, but past researchers have suggested that trainers should prepare materials with nontechnical language and supplemental diagrams that illustrate the progression of steps or guidelines for arranging the materials (e.g., Graff & Karsten, 2012;Severtson & Carr, 2012). Self-instruction may be delivered in a computer-based format in which quizzes are embedded and staff members receive immediate, automated feedback on their answers; trainers can also program computer-based instruction such that staff members may not advance to later content without mastering earlier content (e.g., Nosik et al, 2013).…”
Section: Self-instruction Description and Rationale For Self-instructionmentioning
confidence: 99%
“…In a search of the extant literature, we identified ten studies that trained staff to implement SPAs (Bishop and Kenzer 2012); Graff and Karsten (2012b); (Lavie and Sturmey 2002;Lerman et al 2008;Lerman et al 2004;Pence et al 2012;Rosales et al 2015;Roscoe and Fisher 2008;Roscoe et al 2006;Weldy et al 2014). No previous study trained staff to implement all four components previously discussed.…”
mentioning
confidence: 99%
“…For example, research has only begun to address how to maximize the effects of written instruction (e.g., Graff and Karsten 2012) and modeling (e.g., Catania et al 2009;Moore and Fisher 2007), the need for rehearsal (e.g., Ward-Horner and Sturmey 2012), or the type and frequency of performance feedback (e.g., Pence et al 2014;Wood et al 2007). Perhaps more importantly, the extent to which organizations adopt empirically supported training and performance management practices for use with staff is unknown.…”
mentioning
confidence: 99%